The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2004
DOI: 10.1590/s0034-71672004000200015
|View full text |Cite
|
Sign up to set email alerts
|

Tendências da temática qualidade de vida na produção científica de enfermagem

Abstract: ResumoO presente estudo caracteriza-se como uma pesquisa bibliográfica da temática qualidade de vida, empreendida nas Bases de dados BDENF e LILACS, na Biblioteca virtual da BIREME. Foram pesquisados também nas revistas de enfermagem classificadas como B e C internacional e B nacional pelo QUALIS/ CAPES. Os resultados obtidos indicam que a produção de conhecimento acerca da temática em pauta se limita a situações de agravos à saúde especialmente a grupos específicos. A produção ainda está restrita a cursos de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
1
0
6
Order By: Relevance
“…Se nota que hay todavía una cultura de la práctica de la Enfermería situada en cuidados curativos, hospitalocéntrica, en el modelo biomédico, lo que aleja la fundamentación de esta pautada en acciones básicas de Promoción de la Salud (23) .…”
Section: A Modo De Reflexiónunclassified
“…Se nota que hay todavía una cultura de la práctica de la Enfermería situada en cuidados curativos, hospitalocéntrica, en el modelo biomédico, lo que aleja la fundamentación de esta pautada en acciones básicas de Promoción de la Salud (23) .…”
Section: A Modo De Reflexiónunclassified
“…We observed that the biomedical model is still present in the studies developed by the academics and the existence of a culture focused on a hospital-centered curative caren guides the practice of nursing, leading the production of knowledge unrelated to the focus of Primary Health Care (PHC). 28 The Family Health Strategy (FHS) was another significant focus option for teachers, an important locus for the use of soft technologies by nurses. In this environment, the nurse is responsible and is a fundamental professional in the monitoring of SUS patients and when working in the FHS make use of different technologies that include both the technical-care and the technical-relational dimensions that include the interactions between users and families as well as the collective-social dynamics of those involved in the work process, thus contributing to the planning of the continuity of the expansion of FHS care and strengthening the PHC.…”
Section: Discussionmentioning
confidence: 99%
“…Outra realidade importante a ser destacada é com relação ao perfil de saúde da população investigada. Ao serem questionadas sobre a presença ou não de problemas de saúde, 94,6% da amostra afirmou possuir Sabe-se que uma boa qualidade de vida depende de condições objetivas, tais como saúde, atividade, níveis de renda, escolaridade, estilo de vida, entre outros, e depende, ainda, de condições subjetivas, como o bem-estar psicológico e emocional (15) . No presente estudo, ao se referirem à sua imagem corporal com palavras de conotação negativa, infere-se que tratou-se de pessoas que podem ter passado por situações de discriminação por serem mais velhas.…”
Section: Discussionunclassified